2017
DOI: 10.5152/tud.2017.76032
|View full text |Cite
|
Sign up to set email alerts
|

The role of vitamin D supplementation on erectile function

Abstract: In the last few years growing evidence highlighted vitamin D (VD) deficiency is one of the several dynamics that associates with increased atherosclerotic cardiovascular (ASCV) diseases. ASCV diseases and erectile dysfunction (ED) share common risk factors such as diabetes mellitus, hypertension, smoking, hyperlipidemia, and a sedentary lifestyle. The aim of this review was to summarize current progress in VD research by focusing effect of low VD level on different body systems and erectile function. Here we e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 53 publications
(100 reference statements)
1
14
0
2
Order By: Relevance
“…Of note, the antioxidant pathway of vitamin D is also mediated by the activation of the Mek/Erk-Sirt1 axis [ 24 ]. In addition, activated vitamin D stimulates the production of nitric oxide in endothelial cells and nitric oxide synthases, a key process to penile vascular dilation [ 25 , 26 ]. Furthermore, it also plausible that vitamin D binds directly to the androgen receptor as suggested by computer (in silico) models which show that besides activating the vitamin D receptor, 1,25(OH) vitamin D also has affinity for several other nuclear receptors, such as ɑ / β thyroid receptors, glucocorticoid receptor, and androgen receptor.…”
Section: Discussionmentioning
confidence: 99%
“…Of note, the antioxidant pathway of vitamin D is also mediated by the activation of the Mek/Erk-Sirt1 axis [ 24 ]. In addition, activated vitamin D stimulates the production of nitric oxide in endothelial cells and nitric oxide synthases, a key process to penile vascular dilation [ 25 , 26 ]. Furthermore, it also plausible that vitamin D binds directly to the androgen receptor as suggested by computer (in silico) models which show that besides activating the vitamin D receptor, 1,25(OH) vitamin D also has affinity for several other nuclear receptors, such as ɑ / β thyroid receptors, glucocorticoid receptor, and androgen receptor.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, a study in diabetic rats showed the ability of maxacalcitol, an analogue of vitamin D, to improve the antioxidant pathway of nuclear factor erythroid 2-related factor 2 (Nrf2) [31]. Inflammation can exert its detrimental action on the endothelium through both chronic low-grade inflammation, associated with atherosclerotic mechanisms, and by the acute systemic inflammatory response [32]. Vitamin D exerts an immunomodulatory action thus reducing inflammation.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, it has been shown that vitamin D is able to stimulate the expression eNOS and therefore the production of nitric oxide (NO), a key molecule in the erectile response. Hence the reduction of NO production in patients with vitamin D deficiency could be another mechanism that explains its correlation with ED [32].…”
Section: Discussionmentioning
confidence: 99%
“…Khazan 2015). In diabetics the anti-inflammatory effects of NO are very beneficial (Talib 2017). The high level of NO is toxic for health and can cause bodily dysfunction (Khazan 2015).…”
Section: Polymorphism Vdr Fokimentioning
confidence: 99%